2020
DOI: 10.12890/2020_001394
|View full text |Cite
|
Sign up to set email alerts
|

She Has The Blues: An Unusual Case of Copper Sulphate Intoxication

Abstract: Background: Copper is an essential trace element of the human body. However, it is related to many diseases. Copper intoxication is not common in Western countries, but needs to be rapidly recognised because of its high lethality. Case presentation: We report the case of a 40-year-old woman who presented to the emergency department after performing intrarectal administration of a blue powder sent from Cameroon by her family, in the belief that this would help her to get pregnant. Her evolution was complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…D-penicillamine, dimercaprol, and edentate calcium diphosphate (EDTA) can chelate copper and enhance its elimination by the urinary tract. In our case, because the result of the blood analysis did not reveal copper level in the toxic range, chelation therapy was not performed [7,10]. Andreja SINKOVIC et al reported that the use of 2,3-dimercaptopropane-l-sulphonate (DMPS) was beneficial in the treatment of intentional oral poisoning [26].…”
Section: Diagnosis and Treatmentmentioning
confidence: 83%
See 2 more Smart Citations
“…D-penicillamine, dimercaprol, and edentate calcium diphosphate (EDTA) can chelate copper and enhance its elimination by the urinary tract. In our case, because the result of the blood analysis did not reveal copper level in the toxic range, chelation therapy was not performed [7,10]. Andreja SINKOVIC et al reported that the use of 2,3-dimercaptopropane-l-sulphonate (DMPS) was beneficial in the treatment of intentional oral poisoning [26].…”
Section: Diagnosis and Treatmentmentioning
confidence: 83%
“…The duodenum function in reabsorbing the bile and pancreatic secretions plays an important role in the complexity of the analysis of copper bioavailability. Elimination through the kidneys only consists of a small part (< 5%) [10].…”
Section: Copper Physiology and Physiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…2 A high concentration of copper ions depletes cellular glutathione stores with subsequent production of reactive oxygen species, leading to oxidative stress and membrane toxicity in red cells, hepatocytes, myocytes, and other cells. 1,3…”
Section: Discussionmentioning
confidence: 99%
“…Free copper binds to albumin forming its toxic form [2] . Blue-green material in emesis or stool is highly suggestive of copper ingestion and can be the only clue to diagnosis [3,4] . In this case, it was possible to confirm the drugs ingested, which is important for clinical management.…”
Section: Discussionmentioning
confidence: 99%